2020
DOI: 10.3389/fendo.2020.00004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Hashimoto's Thyroiditis–Related Thyroid Hormone Levels and 25-Hydroxyvitamin D

Abstract: The purpose of this study was to further clarify the association of Hashimoto's thyroiditis (HT) and vitamin D deficiency, and to seek the connection between them and related influencing factors. Methods: Data were obtained from subjects who underwent health examinations from January 2018 to December 2018. The diagnosis of HT was based on: antithyroid peroxidase antibody (TPO-Ab) levels >35 IU/ml and/or antithyroglobulin antibody (Tg-Ab) levels >40 IU/ml. Based on the Endocrine Society guidelines, 25-hydroxyvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 25 publications
4
47
2
1
Order By: Relevance
“…The most similar study to ours, by sample size and result, was reported by Kim et al [ 47 ] who observed a significant negative correlation between vitamin D and serum TSH in the group of 369 AITD patients and 407 controls after adjustment for sample season, age, sex, and BMI (r = −0.127, p = 0.013). Chao et al [ 28 ] also observed a negative correlation and a similar effect to ours between vitamin D and TSH in 5230 participants, of which 373 were HT cases.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The most similar study to ours, by sample size and result, was reported by Kim et al [ 47 ] who observed a significant negative correlation between vitamin D and serum TSH in the group of 369 AITD patients and 407 controls after adjustment for sample season, age, sex, and BMI (r = −0.127, p = 0.013). Chao et al [ 28 ] also observed a negative correlation and a similar effect to ours between vitamin D and TSH in 5230 participants, of which 373 were HT cases.…”
Section: Discussionsupporting
confidence: 86%
“…The next important observation of our study is a nominally significant weak negative correlation between vitamin D levels and TSH in all HT patients ( Table 4 ). The majority of studies observed significant associations between vitamin D deficiency and TSH values in HT patients or weak negative correlations between vitamin D levels and TSH [ 28 , 46 , 47 , 48 ]. The most similar study to ours, by sample size and result, was reported by Kim et al [ 47 ] who observed a significant negative correlation between vitamin D and serum TSH in the group of 369 AITD patients and 407 controls after adjustment for sample season, age, sex, and BMI (r = −0.127, p = 0.013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis [including 6/3 studies with continuous/dichotomous 25(OH)D levels] showed that HT patients had lower values compared to controls, and more likely have 25(OH)D deficiency ( Wang et al, 2015 ). Moreover, data on the inverse correlation between vitamin D values with thyroid volume, and duration and severity of HT, and TH and thyroid antibody levels further reinforcing the idea that vitamin D deficiency might play a role in the risk, onset and development of HT ( Muscogiuri et al, 2016 ; Chao et al, 2020 ).…”
Section: Vitamin D and Thyroid Pathophysiologymentioning
confidence: 69%
“…Vitamin D has been found to play an increasingly crucial regulatory role in bone metabolism, the mucosal barrier, and the immune system in the past few decades. More recently, numerous studies have highlighted that an insufficient level of 25-hydroxyvitamin D [25(OH)D] is significantly associated with HT 123 - 125 .…”
Section: Treatments For Ht-related Miscarriagementioning
confidence: 99%